Proposed Nutrient Standards for Plant-Based Beverages Intended as Milk Alternatives - Drewnowski, Adam; Henry, Christiani Jeyakumar; Dwyer, Johanna T. (Frontiers in Nutrition, 2021)
Abstract Background: Plant-based beverages (PBB) that are marketed as alternatives to cow milk are gaining in popularity worldwide. Nutrient quality of PBB can be highly variable. Objective: To develop a set of voluntary or mandatory nutrient standards for the PBB product category in order to assist innovation and guide product development and reformulation. Methods: The present goal was to develop standards for PBB energy content, minimum protein content and quality, maximum content for added fat, sugar, and salt, and to suggest forti-fication levels for selected vitamins and minerals. The standards were based on dietary rec-ommendations and guidelines and current practices of federal agencies in the US.. Results: The proposed energy and nutrient content for PBB milk alternatives are maximum 85-100 kcal energy per 100 g; a minimum for 2.2g/100g of high-quality protein, low content of saturated fat (<0.75 g/100g) and added sugar (5.3-6.25g/100g) and consistent fortification with calcium, vitamins A, D, B-2 and B-12 at levels comparable to those found in cow milk (1%). Ideally, the protein content ought to be increased (2.8g/100g) and added sugar content reduced even further (2.7-3.1g/100g) for “best of class” products. These proposed standards were ap-plied to the 641 existing PBB products listed in the 2018 version of the USDA Branded Food Products Database (BFPDB). The standards were met by less than 5% of the PBB on the US market. Conclusion: Often viewed as equivalent to milk in nutritional value, many PBB are often low in protein and are fortified with varying amounts of calcium, and vitamins A and D. Nutrient standards for this category should be adopted by the food industry, by public health regulatory authorities, and by standardization bodies such as the Codex Alimentarius.